2019
DOI: 10.1111/tpj.14426
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis non‐host defence‐associated coumarin scopoletin protects soybean from Asian soybean rust

Abstract: Summary The fungus Phakopsora pachyrhizi (Pp) causes Asian soybean rust (SBR) disease which provokes tremendous losses in global soybean production. Pp is mainly controlled with synthetic fungicides to which the fungus swiftly develops fungicide resistance. To substitute or complement synthetic fungicides in Asian soybean rust control, we aimed to identify antifungal metabolites in Arabidopsis which is not a host for Pp. Comparative transcriptional and metabolic profiling of the Pp‐inoculated Arabidopsis non‐h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 83 publications
0
48
0
Order By: Relevance
“…We (Table 1). Beyer et al, 2019, demonstrated fungistatic activity of coumarin scopoletin against P. pachyrhizi [49]. Coumarin was able to suppress the formation of pre-infection streaks and penetration of P. pachyrhizi when sprayed on leaves of Arabidopsis, a non-host plant from ASR [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We (Table 1). Beyer et al, 2019, demonstrated fungistatic activity of coumarin scopoletin against P. pachyrhizi [49]. Coumarin was able to suppress the formation of pre-infection streaks and penetration of P. pachyrhizi when sprayed on leaves of Arabidopsis, a non-host plant from ASR [49].…”
Section: Discussionmentioning
confidence: 99%
“…We identified four coumarins, 7-methoxycoumarin [M + H] + m/z 177.0541; [M + H] + m/z 193.0488 scopoletin; xanthyletin [M + H] + m/z 229.0857, and osthole [M + H] + m/z 245.1168 ( Table 1 ). Beyer et al, 2019, demonstrated fungistatic activity of coumarin scopoletin against P. pachyrhizi [ 49 ]. Coumarin was able to suppress the formation of pre-infection streaks and penetration of P. pachyrhizi when sprayed on leaves of Arabidopsis , a non-host plant from ASR [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, feeding rats ochratoxin A, one of the major mycotoxins derived from a coumarin backbone, resulted in increased abundance of a Lactobacillus strain that is able to absorb this metabolite ( Guo et al , 2014 ). In plant roots, secreted coumarins have been recognized as important for increasing bioavailability of iron, through reduction and chelation ( Tsai and Schmidt, 2017 ), and also for their antimicrobial functions ( Beyer et al , 2019 ; Stringlis et al , 2019 ). Interestingly, a transcription factor, MYB72, which controls expression of several genes in coumarin synthesis, is also important for induced systemic resistance against pathogens triggered by the root bacterium Pseudomonas simiae WCS417 ( Zamioudis et al , 2014 ).…”
Section: Plant Secondary Metabolites Shown To Affect the Microbiomementioning
confidence: 99%
“…In addition to the roles of coumarins in iron uptake, in vitro chemical assays showed that several coumarins, such as scopoletin, which is the most abundantly expressed coumarin in low-iron conditions, exhibit direct antimicrobial activities against several pathogens [12,44,45,46]. In any case, scopoletin from seed kernels of Melia azedarach shows synergistic anti-fungal effects when combined with other coumarins [47].…”
Section: Coumarins Shape Microbiome Composition In the Rootsmentioning
confidence: 99%